Autonomic Notification For A Context Aware System Using Push Server Technology (International Journal of Scientific Research and Management (IJSRM), 2017)
The method of autonomic notification for a context aware system using push server technology. Push server technology has developed under the Comet programming model. The Comet investigates basic problems associated with distributed computing in an internet environment with mobile objects .Comet, support mobility in two flavors: physical mobility and virtual mobility. Push technology has evolved to a great extent since its inception and there have been many additions of new features to the available solutions, in terms of reliability, performance and new standards. We propose an application to push data in real time which enables bidirectional flow of data and which is independent of any particular publisher/subscriber. Usually, the file systems are heavily guarded by firewalls and accessing them from a remote location poses problems, our application solves this problem and allows secure access while maintaining the integrity. Server application is called Push Notify which is based on publish/subscribe model and is independent, which enables it to be easily integrated with any file server of any university and with any communication client, to achieve the paradigm, “any publisher, any subscriber”. Communication client for subscribers to receive notifications or alerts can be web browser extension or mobile device application.